Active Smoking Increases Microsomal PGE2-Synthase-1/PGE-Receptor-4 Axis in Human Abdominal Aortic Aneurysms. (30th April 2014) - Dilmé, Jaime-Félix; Solà-Villà, David; Bellmunt, Sergi; Romero, José-María; Escudero, José-Román; Camacho, Mercedes; Vila, Luis
Abstract : Background . The cyclooxygenase- (COX-) 2/microsomal PGE-synthase- (mPGES-) 1/PGE-receptor- (EP-) 4 axis could play a key role in the physiopathology of abdominal aortic aneurysm (AAA) in humans. In this study, we investigated the influence of cardiovascular risk factors on the expression of the PGE 2 pathway in human AAA. Methods . Aortic ( n = 89 ) and plasma ( n = 79 ) samples from patients who underwent AAA repair were collected. Patients were grouped according to risk factors. COX-isoenzymes, mPGES-1, EPs, α -actin, and CD45 and CD68 transcripts levels were quantified by QRT-PCR and plasma PGE 2 metabolites by EIA. Results . Current smoking (CS) patients compared to no-CS had significantly higher local levels of mPGES-1 ( P = 0.009 ), EP-4 ( P = 0.007 ), and PGE 2 metabolites plasma levels ( P = 0.008 ) . In the multiple linear regression analysis, these parameters remained significantly enhanced in CS after adding confounding factors. Results from association studies with cell type markers suggested that the increased mPGES-1/EP-4 levels were mainly associated with microvascular endothelial cells. Conclusions . This study shows that elements of the PGE 2 pathway, which play an important role in AAA development, are increased in CS. These results provide insight into the relevance of tobacco smoking in AAA development and reinforce the potential of mPGES-1 and EP-4 as targets for therapy in AAA patients.